Balancing Multilevel Politics in Local Environmental Policy Choices. (January 2020) - Fowler, Luke; Rabinowitz, Geoffrey
Although local governments are well poised to address complex environmental policy problems, balancing local and supra-local politics is a key obstacle to overcome. The authors argue that when making policy choices, local policymakers balance local and supra-local influences by exploiting uncertainty in policy goals and associated target populations. Using probit models and survey data of city and county agencies, the authors examine how local and supra-local politics influence local policy choices. Four scenarios are identified: (a) pollution prevention and regional cooperation initiatives affected by local politics, (b) outreach initiatives affected by supra-local politics, (c) transportation alternative initiatives affected by both local and supra-local politics, and (d) energy alternatives and smart growth initiatives affected by interactions between local and supra-local politics. The conclusions suggest ambiguity frames environmental policies, which is to local policymakers' advantage when balancing contentious multilevel politics.